2020
DOI: 10.1101/2020.06.02.128892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Membrane potential regulates Hedgehog signaling and compartment boundary maintenance in theDrosophilawing disc

Abstract: The Drosophila wing imaginal disc is composed of two lineage-restricted populations of cells separated by a smooth boundary. Hedgehog (Hh) from posterior cells activates a signaling pathway in anterior cells near the boundary which is necessary for boundary maintenance. Here, we show that membrane potential is patterned in the wing disc. Anterior cells near the boundary, where Hh signaling is most active, are more depolarized than posterior cells across the boundary. Elevated expression of the ENaC channel Rip… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…In planaria, shortly after wounding, membrane depolarization acts as an early anterior signal that is sufficient (even when induced on the posterior side) to promote the consequent formation of all the anterior structures of the planarian head by inducing notum expression, which inhibits β-catenin-dependent Wnt signal transduction (Durant et al, 2019). Furthermore, it was recently revealed that in the Drosophila wing discs, depolarization events promote membrane localization of the transmembrane receptor smoothened to promote Shh signaling and that membrane potential values are patterned within the wing disc (Emmons-Bell and Hariharan, 2021). These discoveries show that electrophysiological changes are important signals in the formation and growth of anatomical structures.…”
Section: Discussionmentioning
confidence: 99%
“…In planaria, shortly after wounding, membrane depolarization acts as an early anterior signal that is sufficient (even when induced on the posterior side) to promote the consequent formation of all the anterior structures of the planarian head by inducing notum expression, which inhibits β-catenin-dependent Wnt signal transduction (Durant et al, 2019). Furthermore, it was recently revealed that in the Drosophila wing discs, depolarization events promote membrane localization of the transmembrane receptor smoothened to promote Shh signaling and that membrane potential values are patterned within the wing disc (Emmons-Bell and Hariharan, 2021). These discoveries show that electrophysiological changes are important signals in the formation and growth of anatomical structures.…”
Section: Discussionmentioning
confidence: 99%
“…To find out how glycolysis affects Smo accumulation, the authors hypothesised that ATPs generated by glycolysis might be responsible for generating differences in plasma membrane potential, that in turn affects the transportation of small inhibitors of Hh signalling. Membrane potential has recently been shown to be patterned in the wing imaginal disc, and disruption of membrane potential alone is sufficient to lead to the stabilisation of Smoothed and Ci155 (preprint: Emmons‐Bell & Yasutomi, 2020). Na + /K + ‐ATPase, or the sodium‐potassium pump, is primarily responsible for utilising ATP to export three sodium ions and import two potassium ions to generate membrane potential.…”
Section: Figure Atp Drives Atpase Pump Membrane Potential and Hh Patmentioning
confidence: 99%
“…Of particular note is the range of time and length scales over which Vmem can influence cellular and organismal physiology. [1][2][3] On short timescales, Vmem changes control neuronal communication and cardiomyocyte contraction. However, all cells, even non-electrically excitable cells, maintain a transmembrane potential, spending an estimated 10-50% of their cellular ATP budget to pump ions in opposing directions.…”
Section: Introductionmentioning
confidence: 99%
“…4 On longer timescales, Vmem displays diverse patterns, including responding to growth factor signals, 5,6 oscillating throughout the cell cycle, 7 and marking developmental boundaries in tissue. 3,8 Further, these voltage signals can be compartmentalized into small areas such as dendritic spines 9 or delocalized over larger tissues. 10 Accurate and non-invasive Vmem recording techniques are required to document and understand the many roles of Vmem.…”
Section: Introductionmentioning
confidence: 99%